Auditory-cortex lesions impair contralateral tone-pattern detection under informational masking - Prilop, Lisa; Gutschalk, Alexander (Cortex, 2017)
Impaired hearing contralateral to unilateral auditory-cortex lesions is typically only observed under conditions of perceptual competition, such as dichotic presentation or speech in noise. It remains unclear, however, if the source of this effect is direct competition in frequency-specific neurons, or if enhanced processing load in more distant frequencies can also impair auditory detection. To evaluate this question, we studied a group of patients with unilateral auditory-cortex lesions (N = 14, six left-hemispheric (LH), eight right-hemispheric (RH); four females; age range 26-72 years) and a control group (N = 25; 15 females; age range 18-76 years) with a target-detection task in presence of a multi-tone masker, which can produce informational masking. The results revealed reduced sensitivity for monaural target streams presented contralateral to auditory-cortex lesions, with an approximately 10% higher error rate in the contra-lesional ear. A general, bilateral reduction of target detection was only observed in a subgroup of patients, who were classified as additionally suffering from auditory neglect. These results demonstrate that auditory-cortex lesions impair monaural, contra-lesional target detection under informational masking. The finding supports the hypothesis that neural mechanisms beyond direct competition in frequency-specific neurons can be a source of impaired hearing under perceptual competition in patients with unilateral auditory-cortex lesions.
Gesehen am 24.05.2018